2002
DOI: 10.1074/jbc.m206494200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the IκB-kinase NEMO Binding Domain

Abstract: Proinflammatory activation of NF-B requires an upstream kinase complex (IB-kinase; IKK) composed of two catalytic subunits (IKK␣ and IKK␤) and a noncatalytic regulatory component named NEMO (NF-B essential modulator). NEMO interacts with a COOH-terminal sequence within both IKKs termed the NEMO-binding domain (NBD), and a cell-permeable NBD peptide blocks NEMO/IKK␤ interactions and inhibits tumor necrosis factor-␣-induced NF-B. We report here that a peptide encompassing the NBD not only blocked association of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
191
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 149 publications
(212 citation statements)
references
References 43 publications
21
191
0
Order By: Relevance
“…We found that the NF-B pathway was strongly inhibited when pre-B lymphocytes were preincubated with BA-CC2 (IC 50 ϭ 22 M) or BA-LZ (IC 50 ϭ 3 M). The latter value is about 2 orders of magnitude lower than that of the previously described pep- tide used to disrupt the NEMO/IKK interface (13,37). Similar values were obtained when we assayed the DNA binding capacity of NF-B using the TransAM TM NF-B p65 Chemi kit provided by Active Motif Inc. (data not shown).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…We found that the NF-B pathway was strongly inhibited when pre-B lymphocytes were preincubated with BA-CC2 (IC 50 ϭ 22 M) or BA-LZ (IC 50 ϭ 3 M). The latter value is about 2 orders of magnitude lower than that of the previously described pep- tide used to disrupt the NEMO/IKK interface (13,37). Similar values were obtained when we assayed the DNA binding capacity of NF-B using the TransAM TM NF-B p65 Chemi kit provided by Active Motif Inc. (data not shown).…”
Section: Discussionsupporting
confidence: 48%
“…In a previous study, a cell-permeable peptide corresponding to the C terminus of IKK-␣ and IKK-␤ was used to compete with the binding of NEMO, thereby preventing the assembly of the IKK complex and blocking activation of the kinases (13,37). Other cell-permeable peptides have been designed to interfere with the NF-B pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The housekeeping gene ␤-actin was used as an internal control. Total RNA (7 g) was reverse-transcribed into complementary DNA by using oligo(dT) [12][13][14][15][16][17][18] primer (Invitrogen) and Superscript II reverse transcriptase (Invitrogen). Complementary DNA (1 l) was amplified by PCR using Taq polymerase (Promega, Madison, WI) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Investigators in our group have previously reported that an NH 2 -terminal ␣-helical region of NEMO associates with a hexapeptide sequence within the extreme COOH-terminus of both IKK␣ and IKK␤, and we have named this region the NEMO-binding domain (NBD) (12,13). Our group also found that a short cell-permeable peptide spanning the IKK␤ NBD, which we named NBD peptide, disrupted the association of NEMO with IKKs in vitro and blocked TNF␣-induced NF-B activation in vivo.…”
mentioning
confidence: 99%
“…Plasmids and Antibodies-Expression vectors encoding FLAG-tagged human full-length NEMO, NEMO , NEMO 1-100 , wild type and dominant negative IKK␤, Xpress-IKK␣, and Xpress-IKK␤ have been described elsewhere (26). The 3xB firefly luciferase reporter plasmid and the Renilla luciferase reporter plasmid were described previously (27).…”
Section: Methodsmentioning
confidence: 99%